NURSES' EXPERIENCES IN ESTABLISHING INDEPENDENT NURSING PRACTICE BUSINESSES IN SINGKAWANG, WEST KALIMANTAN, IN 2023 - Christian Alvyanto (PT. Radja Intercontinental Publishing, 2026)
This study aims to explore nurses' experiences in establishing independent nursing practice businesses in Singkawang, West Kalimantan, in 2023. The study used a qualitative approach with a phenomenological design. The participants were two nurses who had established and operated independent nursing practice/home care services. Data were collected through in-depth interviews, field notes, and supporting documents, and were analyzed inductively using Colaizzi's stages. The findings revealed seven main themes: fulfillment of administrative and legal requirements, possession of competency certificates and work experience, financial readiness, communication with clients, adequate facilities and infrastructure, standardized medical equipment and reserve stock, and relationships with patients and work partners. The study concludes that the successful establishment of independent nursing practice is determined not only by clinical competence, but also by regulatory compliance, managerial ability, capital readiness, therapeutic communication, and community trust.